The forecasted estimation of greenhouse gas emissions from the use of natural gas in the economy of Ukraine - Stanytsina V.V.; Panchenko G.G. (General Energy Institute of the National Academy of Sciences of Ukraine, 2021)
The article presents a retrospective review of natural gas consumption and greenhouse gas emissions from its consumption. It is determined that greenhouse gas emissions in the country as a whole decreased from 1990 to 2019 by 62.4%, emissions from natural gas consumption – by 71.7%.The potential for energy saving from structural changes in the economy is determined at the level of 5.2 billion m3 and the technological potential for energy saving from the introduction of energy saving measures and replacement of natural gas with other fuels in heat generating plants, including measures implemented in household sector, at the level of 7.5 billion m3 in 2040.Using the method of forecasting long-term demand for energy resources developed at the Institute of General Energy, the forecast of natural gas demand in Ukraine until 2040 is developed for the conservative scenario of economic development taking into account structural changes and technological energy saving in the country and enlarged sections of the economy. Slight growth in natural gas demand is projected to reach 32.9 billion m3 in 2040.The forecast of greenhouse gas emissions only from the use of natural gas by consumer groups and by the country as a whole is calculated.According to the assumption of moderate economic growth and the implementation of energy-saving measures, it is expected to reduce greenhouse gas emissions from natural gas use in 2030 (compared to 2017) and gradually increase after 2030. Therefore, to reduce greenhouse gas emissions after 2030, it is necessary to implement measures and technologies for the decarbonization of the country's economy.To assess the capability of meeting the target already set in Ukraine's 2nd National Contribution to the Paris Agreement, it is necessary to determine projected emissions not only from the use of natural gas but also from the use of coal and petroleum products, and to estimate emissions from other sources, including leakages. Determining the estimation of greenhouse gas emissions from leakages is a separate task.The obtained results allow to determine the largest sources of greenhouse gas emissions from natural gas consumption in the country's economy and to focus further research on identifying ways to reduce emissions.